Approaching Empedocles through PWL practices - Lucio Angelo Privitello (Eidos. A Journal for Philosophy of Culture)
To approach the poem-fragments of Empedocles as a discourse emerging from the drama of living, is to allow their performatively theorized snapshots to return from mere stills to moving images of practice in modulated stages of training. This study will propose two ways of approach: aesthetically, and as a transformative spiritual exercise (askēsis). The aesthetic way employs four terms from Adorno’s Aesthetic Theory, and the way of spiritual exercise follows Hadot’s four stages of a Goethe inspired practice from his text, Don’t Forget to Live. Adorno’s four terms (fragmentary, enigmatic, fixated, shudder), work as a frame for Empedocles’ poem-fragments (and those of other Presocratics), that dovetails with PWL practices, and examples of self-transformation, both personal and historical. Nested within each of Hadot’s four stages, including a conclusion on the “deaths of Empedocles,” I have placed and re-ordered a selection of Empedocles’ fragments in my translation that reframe the poem-fragments back to their continuing ways of coming back to life as memento vivere. This study, stages, and examples serve as a guide to a larger project involving a re-translating and re-sequencing (re-ordering) of all of Empedocles’ extant fragments. Such a task hopes to add to the PWL’s cartographic and hermeneutic project of the arts of living, teachers of ways of living, and as an alternative and vibrant history of philosophy.